Illegal immigration in the eastern Aegean Sea: a new source of marine litter - KATSANEVAKIS, S. (Mediterranean Marine Science, 2015)
The maritime area dominates the current increasing wave of illegal immigration to Europe. The Greek islands of the eastern Aegean Sea are the main entrance points of immigrants arriving from the coasts of Turkey. Immigration to the Greek islands is mainly conducted with inflatable boats, which are abandoned upon arrival along the coasts together with other items such as life-jackets, inflatable tubes, and clothing. This novel type of marine litter dominates many beaches and becomes increasingly abundant. Two beaches in Lesvos Island were surveyed for marine litter, and immigration-related items were found to account for more than 97% of marine litter by weight. Immigration-related littering adds pressure on marine biodiversity and the local economy, impacting the recreational value of beaches.